THE RECONSTRUCTION OF INDONESIAN SHIPPING LAW IN THE SEA TRANSPORTATION SYSTEM FOR A SUCCESSFUL SEA TOLL PROGRAM AND IMPROVEMENT OF SHIPPING ADMINISTRATION - Victoria, Ong Argo; Pambudi, M. Aji Luhur; Dewi, Ratna K. (International Journal of Law Reconstruction, 2022)
Indonesia uses Pancasila Democracy as the main foundation as well as a source of law in the nation and state (staatfundamentalnorm). One of the sounds of the 5th principle of Pancasila is, "Social Justice for All Indonesian People" which means fair to fellow human beings, fair to oneself and fair to God (Pancasila Justice Value). The purpose of this justice in particular must cover the growing system of exploitation of authority and ambiguity in the shipping world from the strong to the weak and must also narrow the socio-economic gap in the lives of seafarers, so that prosperity is achieved that reflects that Indonesia deserves to be called a World Maritime Axis Country as in history. Srivijaya & Majapahit. However, the fair principle has not been fully enforced and there is discrimination, especially the application of several articles in Act No. 17 of 2008 concerning Shipping. This research is a qualitative research with constructivism paradigm and sociological juridical approach. The formulation of the problem in this thesis are; 1) Why is Act No.17 of 2008 concerning Shipping in the Indonesian Sea Transportation System Not Fairly Pancasila?, 2) What are the Weaknesses of Act No.17 of 2008 concerning Shipping that Affects the Suboptimal Sea Transportation System in the Success of the Toll Program Sea and Shipping Administration in Indonesia?, and 3) How to Reconstruct Act No. 17 of 2008 concerning Shipping in the Sea Transportation System for the Success of the Sea Toll Program and Improvement of Indonesian Shipping Administration based on Pancasila Justice Value? The purpose of writing this thesis is to reconstruct several articles in Act No. 17 of 2008 concerning Shipping which contain weaknesses in the Sea Transportation System for the Success of the Sea Toll Program and the Improvement of Indonesian Shipping Administration Based on Pancasila Justice Value. The results of this research are that there are several reconstructions of articles, namely Article 28 paragraph (6) in terms of granting ship operating permits held by the Directorate General, Syahbandar and specifically ASDP by the Land Transportation Management Center (BPTD), Article 59 is reconstructed with the addition of revocation of one's authority to become a crew member in the event of a serious criminal offense. Article 61, paragraph (3) is reconstructed with the addition of ship requirements and specifications. Article 151 (1) is reconstructed with the addition of a paragraph that regulates the affirmation of the welfare of seafarers and Article 169 (1) is reconstructed by giving criminal sanctions not only administrative sanctions. It is hoped that with this reconstruction the Sea Transportation system in the Sea Toll Program will be able to improve the Shipping Administration System in Pancasila Justice Value.